Elsholtzia bodinieri Vaniot ameliorated acute lung injury in mice by regulating pyroptosis, inflammation, oxidative stress and macrophage polarization. (10th May 2023) - Jiang, Xiaoqian; Sun, Jin; Guo, Shancheng; Zhao, Zhiye; Chen, Yuxu; Cao, Jianxin; Liu, Yaping; Cheng, Guiguang; Tian, Lei; Li, Ye
Abstract: Ethnopharmacological relevance: Elsholtzia bodinieri Vaniot, perennial herbs, a traditional Yunnan Chinese herbal medicine. Its whole herb can be used as commonly used herbs to cure fever, headache, inflammation, indigestion etc., and its tender tip can also be used as tea in Yunnan of China. However, the protective mechanism of Elsholtzia bodinieri Vaniot on acute lung injury (ALI) still needs to be explored. Aim of study: ALI is characterized by acute respiratory inflammation, which remains a significant source of morbidity and mortality. The current study with the aim of determining the therapeutic the efficacy of E. bodinieri Vaniot on lipopolysaccharide-induced ALI, moreover uncovered the underlying gene-regulated framework, so E. bodinieri Vaniot might serve as functional food for adjuvant therapy or therapeutic agent. Materials and methods: These potential pharmacological targets of E. bodinieri Vaniot against ALI were analyzed by multiple bioinformatics databases. E. bodinieri Vaniot methanol extract (EBE) was obtained by ultrasonic-assisted extraction method, and detected by UHPLC-ESI-HRMS/MS. These pyroptosis, inflammation and oxidative stress associated factors were measured using ELISA assay, western blotting, and histopathological examination to assess the effects of EBE. EcoTyper and immunofluorescence staining were employed to estimate macrophage polarization states in ALI lungs tissue. Results: In ALI lung tissues, EBE treatment could increase B cell leukemia/lymphoma 2 (BCL2) to inhibit pyroptosis, downregulate prostaglandin-endoperoxide synthase 2 (PTGS2) to attenuate inflammation, upregulating NAD(P)H dehydrogenase, quinone 1 (NQO1) to alleviate oxidative stress and induce macrophage polarization toward the M2 phenotype. Conclusion: E. bodinieri Vaniot ameliorated ALI thought regulating pyroptosis, inflammation, oxidative stress and macrophage polarization, as well as could be a promising source for therapeutic agent. Graphical abstract: Image 1 Highlights: The potential pharmacological targets of E. bodinieri Vaniot against ALI were BCL2, PTGS2 and NQO1. EBE treatment suppressed pyroptosis of ALI by upregulating BCL2. EBE treatment attenuated inflammation of ALI by downregulating PTGS2. EBE treatment alleviated oxidative stress of ALI by upregulating NQO1. EBE treatment induced macrophage polarization toward the M2 phenotype in ALI lungs tissue.